9. PREVALENSI DIROFILARIASIS PADA ANJING LOKAL (Canis domestica) DI KECAMATAN LHOKNGA ACEH BESAR SECARA PATOLOGI ANATOMIS Prevalence of Dirofilariasis on Local Dogs (Canis domestica) in Lhoknga Aceh Besar Using Phatological Anatomy Method - Mubarak Assady (Universitas Syiah Kuala, 2016)
The aim of this research was to find out the prevalence of Dirofilaria immitis on local dog in Lhoknga Aceh Besar. This study used 30 local dogs collected from 5 villages in Lhoknga Aceh Besar. Dogs were injected intravenous with phenobarbital at dose of 2-3 mg/kg body weight, then necropsied to find out Dirofilaria immitis in dog heart. The result showed that 3 out of 30 dogs were positive dirofilariasis, two dogs from Nusa village and one dog from Lampaya village. In conclusion, the prevalence of dirofilariasis on local dogs in Lhoknga Aceh Besar is 10%. ____________________________________________________________________________________________________________________ Key words: prevalence, Dirofilaria immitis, dogs, necropsy